In Memoriam Professor Eugeniusz Kozaczka - LINDE, Bogumił; KOCHAŃSKA, Iwona (Archives of Acoustics, 2025)
Professor Eugeniusz Tadeusz Kozaczka, member of the Polish Academy of Sciences, passed away on May 27, 2025, in Gdynia. We write these words with profound sorrow and deep regret, mourning the loss of such an exceptional person as Professor Eugeniusz Kozaczka.